2000
DOI: 10.1042/bst0280033
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 transcription factor contributes both to the basal expression of glutathione S-transferases in mouse liver and to their induction by the chemopreventive synthetic antioxidants, butylated hydroxyanisole and ethoxyquin

Abstract: An overview is provided of the cancer chemoprevention actions of phenolic antioxidants and 6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline (ethoxyquin). These agents principally appear to exert their beneficial effects through induction of phase II drug-metabolizing enzymes such as glutathione S-transferase (GST). The requirement for oxidative metabolism of the synthetic antioxidants to carbonyl-containing compounds, including quinones, in order that they can induce gene expression is discussed. Previous work ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
174
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(189 citation statements)
references
References 19 publications
10
174
2
3
Order By: Relevance
“…Direct evidence for this finding is provided by the observed reduced basal expression of GCL and other Phase II detoxification enzymes in Nrf2-null mice (17,(19)(20)(21). These mice also display a marked increased susceptibility to toxicological insult (17,(19)(20)(21).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Direct evidence for this finding is provided by the observed reduced basal expression of GCL and other Phase II detoxification enzymes in Nrf2-null mice (17,(19)(20)(21). These mice also display a marked increased susceptibility to toxicological insult (17,(19)(20)(21).…”
mentioning
confidence: 72%
“…Several lines of evidence [e.g., Nrf2-null mice, Nrf2 overexpression systems, and Nrf2-dominant negative mutants (17,(19)(20)(21)(30)(31)(32)] implicate this transcription factor as a central transcriptional regulator of ARE-containing Phase II detoxication genes. For example, Nrf2-null mice share remarkable similarity to old animals, including loss of constitutive GCL levels and activity and a concomitant decline in GSH (22).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf1 and Nrf2 Regulate a Similar Subset of Antioxidant Genes-Our previous studies and those of others have demonstrated a critical role for Nrf2 in regulating expression of genes encoding antioxidants (33,38,39). For example, Nrf2 has been shown to regulate expression of both the catalytic and regulatory subunits of ␥-glutamylcysteine ligase (Gclc and Gclm) that is involved in glutathione biosynthesis (26,40).…”
Section: Apoptosis In Compound Nrf1ϫ/ϫ Nrf2ϫ/ϫ Fibroblasts Correlatesmentioning
confidence: 99%
“…A unique cis-acting regulatory sequence, termed the antioxidant response element (ARE), is essential for the constitutive and induced expression of many antioxidant genes involved in the phase II pathway (Friling et al, 1990;Rushmore et al, 1991;Nguyen et al, 2000). Several lines of evidence suggest that NF-E2-related factor 2 (Nrf2) is an important transcription factor responsible for upregulating ARE-mediated gene expression (Itoh et al, 1997(Itoh et al, , 1999Alam et al, 1999;Hayes et al, 2000;Ishii et al, 2000). Studies that use knock-out mice have shown that Nrf2 was part of a transcription factor complex required for regula-tion of the mouse glutathione S-transferase (GST) and NADPH: quinone oxidoreductase (NQO1) genes (Itoh et al, 1997;Hayes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that NF-E2-related factor 2 (Nrf2) is an important transcription factor responsible for upregulating ARE-mediated gene expression (Itoh et al, 1997(Itoh et al, , 1999Alam et al, 1999;Hayes et al, 2000;Ishii et al, 2000). Studies that use knock-out mice have shown that Nrf2 was part of a transcription factor complex required for regula-tion of the mouse glutathione S-transferase (GST) and NADPH: quinone oxidoreductase (NQO1) genes (Itoh et al, 1997;Hayes et al, 2000). In addition, Nrf2/small Maf heterodimers bind to the ARE sequence with high affinity during regulation of the GST and NQO1 genes (Venugopal and Jaiswal, 1996).…”
Section: Introductionmentioning
confidence: 99%